State Bar of California Annual Meeting Held in Century City - Watkins, Howard::::::::: (1987)
Orville A. "Jack" Armstrong, Jr., Mary Dean Armstrong, Regan Anderlini, and Terry Anderlini Armstrong was 1986-87 State Bar President; Terry Anderlini 1987-88 President